Surgical intervention in childhood intermittent exotropia: current practice and clinical outcomes from an observational cohort study. Issue 10 (11th August 2012) - Buck, Deborah; Powell, Christine J; Sloper, John J; Taylor, Robert; Tiffin, Peter; Clarke, Michael P
Abstract : Purpose: To describe surgical outcomes in intermittent exotropia (X(T)), and to relate these to preoperative and surgical characteristics. Methods: 87 children (aged <11 years) underwent surgery in 18 UK centres; review data (mean 21 months post-surgery) were available for 72. The primary outcome measure was motor/sensory outcome (angle and stereoacuity). The secondary outcome measure was satisfactory control assessed by Newcastle Control Score (NCS). Results: 35% of patients had excellent, 28% had fair and 37% had poor primary outcome. Preoperative and surgical characteristics did not influence primary outcome. Satisfactory control was achieved in 65% of patients, while X(T) remained/recurred in 20%. Persistent over-correction occurred in 15% of children. There was no relationship between over-correction and preoperative characteristics or surgical dose/type. Median angle improved by 12 prism dioptres (PD) at near and 19 PD at distance (p<0.001). Median NCS improved by 5 (p<0.001). 40% of those initially over-corrected remained so by last postoperative assessment; no relationship was found between an initial over-correction and good outcome. Conclusions: Whilst excellent motor/sensory outcome was achieved in one-third and satisfactory control in two-thirds of patients, the 37% poor outcome and 15% persistent over-correction rate is of concern. Surgical dose was similar in those under- and over-corrected, suggesting that over-corrections cannot be avoided merely by getting the dosage right: a randomised controlled trial (RCT) would shed light on this issue. Initial over-correction did not improve the chance of a good outcome, supporting the growing literature on this topic and further highlighting the need for randomised controlled trials of X(T) surgery.